2009
DOI: 10.1111/j.1476-4431.2009.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical abnormalities in endurance horses eliminated from competition for medical complications and requiring emergency medical treatment: 30 cases (2005–2006)

Abstract: Based on the results of this study, the prognosis for horses requiring emergency veterinary treatment after being removed from endurance competition (for metabolic reasons) appears to be good if horses are withdrawn from competition under the same criteria outlined in this study. Biochemical abnormalities tend to be mild and do not necessarily aid in delineating sick horses from successfully completing horses. None of the horses with gastrointestinal disease required abdominal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 11 publications
9
74
2
6
Order By: Relevance
“…No differences were noted in electrolyte concentration (Na, K, Cl) in blood of endurance horses that were eliminated from competitions compared with those that successfully completed the competitions (Fielding et al, 2009). High electrolyte losses are usually noted in poorly trained horses, which get tired easily.…”
Section: Discussionmentioning
confidence: 89%
“…No differences were noted in electrolyte concentration (Na, K, Cl) in blood of endurance horses that were eliminated from competitions compared with those that successfully completed the competitions (Fielding et al, 2009). High electrolyte losses are usually noted in poorly trained horses, which get tired easily.…”
Section: Discussionmentioning
confidence: 89%
“…This was probably due to oxidative stress and the common source of these substances: the contracting muscle tissues. A blood lactate concentration of ≥ 4 mmol/l denotes an unfit horse in training protocols (Dudley and Terjung 1985;Guhl et al 1996;Hinchcliff et al 2002;Castejon et al 2006;Kedzierski et al 2009;Fielding et al 2009;Lindner et al 2009). Lactate is a scavenger of free radicals; however, the formation of lactate cannot be divorced from metabolic acidosis which could exhibit pro-oxidant activity and lactic acidosis has been associated with the generation of free radicals and lipid peroxidation (Bralet et al 1991;Groussard et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified higher plasma protein, hematocrit or both in horses that are eliminated from endurance racing or which require treatment for metabolic derangements. [23][24][25] Supporting this finding, a large-scale study of endurance horses competing in races of 72 to 169 km in length found both PCV and plasma protein concentration to provide good prediction ability for metabolic elimination. 21 Plasma protein concentrations had greater sensitivity and specificity for this purpose than PCV, perhaps reflecting the confounding impact of splenic contraction on PCV.…”
Section: Muscle Enzyme Activitiesmentioning
confidence: 70%